ALK TKI therapy in patients with ALK-positive non-small cell lung cancer and brain metastases: A review of the literature and local experiences. (December 2022) - Cicin, Irfan; Martin, Claudio; Haddad, Carolina Kawamura; Kim, Sang-We; Smolin, Alexey; Abdillah, Arif; Yang, Xue
Abstract: This article reviews the role of ALK tyrosine kinase inhibitors (TKIs) in the literature and provides expert commentary on local use in Argentina, Brazil, China, Russia, South Korea, and Turkey. We identified 56 articles involving patients with ALK -positive non-small cell lung cancer (NSCLC) and brain metastases (BM) treated with ALK TKIs published between January 2000 and June 2021. In first-line settings, central nervous system response rates in clinical trials with alectinib (86–94%), brigatinib (67–78%), and lorlatinib (42–82%) were generally higher than those reported with crizotinib (16–71%). Median progression-free survival in patients receiving crizotinib (5.6–7.4 months) was lower than alectinib (not reached), brigatinib (24.0 months), and ceritinib (10.7–25.2 months). Across these counties, next-generation TKIs are preferred for patients with progressing BM lesions. Although next-generation ALK TKIs demonstrate significant activity in these patients and following progression on crizotinib, access remains a challenge for personalized therapy. Graphical Abstract: ga1 Highlights: Chemotherapy and 1st-generation ALK TKIs offer limited permeability across the BBB. Second- and third-generation ALK TKIs offer improved CNS penetration and potency. A lack of head-to-head data continues to challenge treatment decisions. Identifying molecular resistance is not always feasible in real-world settings. Treatment is influenced by access to molecular testing and targeted therapies.